Faktor-Faktor Makroekonomi terhadap Indeks Harga Saham di Indonesia dan Singapura tahun 2015-2023 - Utami, Adre; Soeindra, Victor (Journal of Management and Bussines (JOMB), 2025)
This study analyzes the influence of macroeconomic variables on the stock price index in Indonesia (IHSG) and Singapore (STI) in the period 2015-2023. Using a quantitative approach, this study examines the influence of inflation, interest rates, exchange rates, and gold prices on the stock price index in both countries. The results of the study show that in Indonesia, inflation, interest rates, exchange rates and gold prices have a significant effect on the IHSG. Meanwhile, in Singapore, inflation, exchange rates and gold prices have a significant effect on the STI while interest rates do not have a significant effect on the STI. The advantage of this study is that it highlights the differences in the influence of macroeconomic factors on the stock market in two countries with different economic characteristics. The conclusion is that this study provides insight for policy makers in formulating market stabilization strategies and becomes a reference for investors in compiling a more resilient investment portfolio.  Keywords: Stock Price Index, Inflation, Interest Rates, Exchange Rates, Gold Prices